Saberes ambientais na profissionalização docente e sua operatividade na prática pedagógica - Dantas, Jonielton Oliveira (2017)
The complexity of the environmental problems generated by the relationship between man and nature, custom humanity on the alert and require an interdisciplinary approach on the part of the segments of society, including teaching professionals. It is true that the complexes environmental problems are amenable to an educational response, however, it is necessary that teachers are imbued with the necessary knowledge for the operation of their pedagogical practice, which pervades teacher training and professionalism. Starting from the concept of professionalization as a personal project of construction of the profession in which the teacher acquires skills and knowledge for the improvement of their pedagogical practice, this work has as guiding question to understand how the environmental knowledge, acquired in teacher training courses, and the professionalization process of teachers are related , and if this knowledge is applied in their pedagogical practices. In order to analyze the relations that the teachers establish between the environmental knowledge gained in courses of continuous formation and their professionalization process, the work pursues the concepts of professionalization, and professionalism to understand the internal and external motivations to teacher. The object this research was teachers that attended courses of improvement and specialization in Environmental Education offered in the Poles of CESAD / UFS within the scope of the Sistema Universidade Aberta do Brasil (UAB) - Open University System of Brazil. The methodological course consisted in selecting the sample of participants from mentioned courses, through the completion of questionnaires with the purpose of extracting essential elements of the sociodemographic and professional profile and his / her pedagogical practice, developed in school spaces, with the perspective of categorizing, systematizing and analyzing collected data based on the Content Analysis methodology. In this sense, the study revealed that the teachers were motivated to seek Environmental Education courses in the perspective of using this knowledge in the professional activity, as a way to add value to the professional career by acquiring and expanding the systematized environmental knowledge, operating them in their daily pedagogical practice. In addition, difficulties in the operationality of environmental knowledge, pointed out by teachers, reveal that they assume the stigma of victims, and transfer responsibility to other factors directly related to the pedagogical practice, but do not assume their co-responsibility as a professional, whose duties reverberate in the epistemological commitment, political, social and environmental.